2022
DOI: 10.1016/j.xphs.2021.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Re-Envisioning Pharmaceutical Manufacturing: Increasing Agility for Global Patient Access

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…The authors recognize that companies are often hesitant to invest in APM, concerned that regulatory authorities are not ready to accept the proposed changes, while the regulators wait for concrete data of product safety, efficacy, and quality. [ 74 ] Even though regulators across the globe have largely encouraged continuous manufacturing technology and APM, it is recognized that real or perceived hurdles may exist. [ 75 ] In spite of this perception a recent FDA internal audit found that products with CM processes tended to be approved in less time and reach the market sooner.…”
Section: Advanced Pharmaceutical Manufacturing—a Functional Definitionmentioning
confidence: 99%
“…The authors recognize that companies are often hesitant to invest in APM, concerned that regulatory authorities are not ready to accept the proposed changes, while the regulators wait for concrete data of product safety, efficacy, and quality. [ 74 ] Even though regulators across the globe have largely encouraged continuous manufacturing technology and APM, it is recognized that real or perceived hurdles may exist. [ 75 ] In spite of this perception a recent FDA internal audit found that products with CM processes tended to be approved in less time and reach the market sooner.…”
Section: Advanced Pharmaceutical Manufacturing—a Functional Definitionmentioning
confidence: 99%
“…Advanced manufacturing technologies such as CM can also help improve domestic manufacturing capabilities, thus alleviating to some degree the constraints from global supply chains. 4 Currently, batch manufacturing is still the most widely utilized production method by the pharmaceutical industry. The transition from batch to CM in the pharmaceutical industry is in its early stage and therefore presents unique challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, the current approach for biomanufacturing peptide and protein therapeutics can limit response time, distribution of medicines, and drive healthcare inequities. This backdrop sets the stage to reimagine drug manufacturing away from current reliance on centralized facilities. ,, …”
Section: Introductionmentioning
confidence: 99%
“…This backdrop sets the stage to reimagine drug manufacturing away from current reliance on centralized facilities. 8,10,11 Cell-free protein synthesis (CFPS) has recently emerged as one potential way to rethink decentralized drug manufacturing. CFPS is a technology that harnesses the transcription and translation machinery from cells, without using living intact cells, to produce peptides and proteins in vitro.…”
Section: ■ Introductionmentioning
confidence: 99%